An Appraisal of the Consortium of Tanzania University and Research Libraries - Msuya, Jangawe; Mungwabi, Hosea (University of Dar es Salaam Library Journal, 2017)
This study investigated factors constraining effective growth of the Consortium of Tanzania University and Research Libraries (COTUL). A mixed research design was employed to gain a deeper insight into the subject matter. Data was collected using interviews, questionnaires and observations. Fifty-eight (58) purposively selected professional librarians participated in this study. The study investigated, among other things: the librarians' level of awareness of COTUL, its organizational structures, strengths and challenges. The findings revealed that librarians ' awareness of COTUL is minimal, hence constraining its growth and that the existing organization structures are not conducive for COTUL to function satisfactorily. A number of challenges were identified including weak sustainable financial base, researchers ' low level of awareness of e-resources, lack of e-resource searching skills and lack of office space. Based on these findings, it is recommended that COTUL should look for permanent and reliable funding sources, sensitize all library staff and top administrators, form an Advisory Board and set up a full-time secretariat and a permanent office premises.